Strategies for Advancing High-Quality Development in the Sports Industry Through Mobile Internet Technologies - Huiya Xing; Min Liu; Hongtu Cui; Yicong Zhong, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The rapid evolution of the digital economy necessitates a corresponding transformation in the sports industry, particularly through the integration of mobile internet technologies. This development is crucial not only for enhancing the industry's competitiveness and global cultural influence but also for addressing the dynamic roles and psychological impacts on young people, who are at the forefront of digital consumption and cultural production in sports. As technological advancements reshape the landscape of cultural and sports production, the sports industry is experiencing significant shifts towards more digitally integrated operations. This paper explores the pathways through which the sports industry can harness digital technologies to improve quality and engagement. It discusses the challenges and opportunities in transforming sports culture in the era of mobile internet, emphasizing the need to delve into the digital culture's meanings and implications. By extending digital engagement in sports, the industry can foster a deeper connection with a global audience and enhance psychological engagement with sports content. The analysis provides insights into strategic choices for advancing digital integration in sports, offering solutions to current challenges and contributing to the broader discourse on digital economy advancements in modern society.